2015
DOI: 10.3389/fmicb.2015.00375
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and comparative genomics of Microviridae in Sphagnum- dominated peatlands

Abstract: Microviridae, a family of bacteria-infecting ssDNA viruses, is one of the still poorly characterized bacteriophage groups, even though it includes phage PhiX174, one of the main models in virology for genomic and capsid structure studies. Recent studies suggest that they are diverse and well represented in marine and freshwater virioplankton as well as in human microbiomes. However, their diversity, abundance, and ecological role are completely unknown in soil ecosystems. Here we present the comparative analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 36 publications
2
76
1
Order By: Relevance
“…The description of a large unsuspected genetic diversity of ssDNA viruses across multiple ecosystems (Ge et al, 2011; Kim et al, 2011; Rosario, Duffy & Breitbart, 2012; Labonté & Suttle, 2013b; Eaglesham & Hewson, 2013; Quaiser et al, 2015; Dayaram et al, 2016), and unique evolutionary patterns including gene exchanges between RNA and DNA genomes (Krupovic, Ravantti & Bamford, 2009; Diemer & Stedman, 2012), have highlighted ssDNA viruses as one of the most intriguing viral groups in viral ecology. So far, two main types of ssDNA viruses have been frequently detected in viromes: eukaryote-infecting CRESS-DNA viruses and bacteriophages from the Microviridae family.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The description of a large unsuspected genetic diversity of ssDNA viruses across multiple ecosystems (Ge et al, 2011; Kim et al, 2011; Rosario, Duffy & Breitbart, 2012; Labonté & Suttle, 2013b; Eaglesham & Hewson, 2013; Quaiser et al, 2015; Dayaram et al, 2016), and unique evolutionary patterns including gene exchanges between RNA and DNA genomes (Krupovic, Ravantti & Bamford, 2009; Diemer & Stedman, 2012), have highlighted ssDNA viruses as one of the most intriguing viral groups in viral ecology. So far, two main types of ssDNA viruses have been frequently detected in viromes: eukaryote-infecting CRESS-DNA viruses and bacteriophages from the Microviridae family.…”
Section: Resultsmentioning
confidence: 99%
“…While these MDA viromes routinely uncover new viruses (Angly et al, 2006; Angly et al, 2009; Wegley et al, 2007; Kim et al, 2008; Willner et al, 2009; Ng et al, 2009; Rosario et al, 2009; Rosario, Duffy & Breitbart, 2009; López-Bueno et al, 2009; Roux et al, 2012a; Roux et al, 2012b; Labonté & Suttle, 2013a; Labonté & Suttle, 2013b; Zawar-Reza et al, 2014; Quaiser et al, 2015; Dayaram et al, 2016; Male et al, 2016; Steel et al, 2016), the MDA step selects for small circular ssDNA templates, and unevenly amplifies linear genome fragments even when pooling independent reactions (Yilmaz, Allgaier & Hugenholtz, 2010; Kim & Bae, 2011; Marine et al, 2014). The alternative linker amplification (LA) or tagmentation (TAG) methods are quantitative (±1.5-fold) for dsDNA viruses, even from low input samples (100 femtograms, Duhaime et al, 2012) but strongly select against ssDNA templates (Kim & Bae, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed majority of viral particles in soils and sediments belonged to single-stranded DNA (ssDNA) viruses, especially Microviridae family26272829. These researches showed that the Microviridae sequences comprised 84.6% of whole virus sequences in the Machair soil sample, 50.3% in the brown earth sample and 74% in Izu-Ogasaware Trench deep-sea sediment.…”
mentioning
confidence: 99%
“…No ssDNA phages with a reduced genome like bacteriophage Mini have been isolated before. The reduced genomes and limited number of genes have also been found in many metagenomic assembled Microviridae phages recovered from soil, human and seawater (Tucker et al ., ; Roux et al ., ; Labonté and Suttle, ; Quaiser et al ., ). A ssDNA phage with a 4.1 kb genome size has been assembled from a metagenome of coastal water (Labonté and Suttle, ).…”
Section: Resultsmentioning
confidence: 97%
“…Prophages attributed to Microviridae were identified in the Bacteroides genomes (Krupovic and Forterre, ). Microviridae ‐associated prophages were also found in Bacteroides genomes, according to the assembled phage genomes from peatlands metagenomics (Quaiser et al ., ). The finding of both capsid and replication initiator genes in the bacterial genome suggests a common ancestor between vB_RpoMi‐Mini and a prophage or a prophage remnant in the genome of Sphingomonadales , and implies a historical integration of ssDNA phage DNA into Alphaproteobacteria.…”
Section: Resultsmentioning
confidence: 97%